Successful treatment of a giant pediatric fusiform basilar trunk aneurysm with surpass flow diverter. (3rd June 2015) - Kan, Peter; Mokin, Maxim; Puri, Ajit S; Wakhloo, Ajay K
Abstract : Fusiform aneurysms present a unique challenge to traditional microsurgical and endovascular treatment because of the lack of a discernible neck and the involvement of parent vessel. Flow diversion has increasingly become the treatment of choice for fusiform aneurysms in the anterior circulation, but its results in the posterior circulation are variable. We report successful treatment of a giant fusiform upper basilar trunk aneurysm with the Surpass flow diverter in an adolescent, and discuss the potential advantages of this emerging technology in the treatment of fusiform posterior circulation aneurysms.